Best Interest Standard in School Health: A Concept Analysis. (February 2022) - Grunin, Laura; Malone, Susan
The bioethical concept of best interest standard is cited in courts across America and considered to be an effective method of managing pediatric health care decision-making. Although the best interest standard is referred to in an abundance of nursing, medical, legal, and bioethical literature, refinement and a clear definition of the concept are lacking in the context of school health. An exhaustive and methodical search was conducted across six databases revealing 41 articles from the past decade. The Wilsonian methodology was used to analyze, refine, and clarify the concept of best interest standard by presenting original case vignettes (model, contrary, related, and borderline) and an innovative conceptual model as it applies to school nursing. This concept analysis provides school nurses with a deeper understanding of the best interest standard to navigate the complex nature of making school health care decisions.